2009
DOI: 10.1161/strokeaha.109.556852
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline and Tissue-Type Plasminogen Activator for Stroke

Abstract: Background and Purpose-New treatment strategies for acute ischemic stroke must be evaluated in the context of effective reperfusion. Minocycline is a neuroprotective agent that inhibits proteolytic enzymes and therefore could potentially both inactivate the clot lysis effect and decrease the damaging effects of tissue-type plasminogen activator (t-PA). This study aimed to determine the effect of minocycline on t-PA clot lysis and t-PA-induced hemorrhage formation after ischemia. Methods-Fibrinolytic and amidol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 27 publications
1
76
0
Order By: Relevance
“…For example, treatment with tissue plasminogen activator and minocycline after stroke resulted in a non-significant, 20% reduction in damage, but animals demonstrated a significant improvement in behavioral tests compared with controls. 28 Future studies should address the behavior of animals treated with anti-inflammatory exDCs to determine the extent of functional sparing.…”
Section: Ex Vivo-derived Dendritic Cells Respond To Inflammatory Factmentioning
confidence: 99%
“…For example, treatment with tissue plasminogen activator and minocycline after stroke resulted in a non-significant, 20% reduction in damage, but animals demonstrated a significant improvement in behavioral tests compared with controls. 28 Future studies should address the behavior of animals treated with anti-inflammatory exDCs to determine the extent of functional sparing.…”
Section: Ex Vivo-derived Dendritic Cells Respond To Inflammatory Factmentioning
confidence: 99%
“…Minocycline doesn't affect the fibrinolytic and amidolytic properties of tPA [63]. Additionally, minocycline was able to extend tPA's time window to 6 hours in an embolic focal ischemia model in rats with similar infarct volumes to tPA treatment at 1 hour post-occlusion (and was also protective without tPA at 4 hours) [64].…”
Section: Combining Minocycline With Tpamentioning
confidence: 99%
“…Minocycline has been shown to decrease plasma MMP-9 levels in multiple studies [63,64]. In fact, an analysis of the Fagan et al [21] study showed that lower MMP-9 levels were found in those treated with tPA and minocycline [65].…”
Section: Combining Minocycline With Tpamentioning
confidence: 99%
“…Minocycline, a semisynthetic tetracycline antibiotic, has shown promise as a neuroprotective agent in animal models with induced spinal cord injury, traumatic brain injury, and ischemic and hemorrhagic stroke. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] It is highly lipophilic, crosses the blood-brain barrier, and acts via several pathways to inhibit microglial activation, reduce migration of T-cells, attenuate neural apoptosis, suppress free radical production, decrease central nervous system expression of chemokines and their receptors, and inhibit matrix metalloproteinases, in particular matrix metalloproteinase-9. In experimental stroke studies, minocycline improved behavioral function and reduced infarction volume and hemorrhagic transformation.…”
mentioning
confidence: 99%